2022
DOI: 10.3389/fonc.2022.1014637
|View full text |Cite
|
Sign up to set email alerts
|

A research update on the antitumor effects of active components of Chinese medicine ChanSu

Abstract: Clinical data show that the incidence and mortality rates of cancer are rising continuously, and cancer has become an ongoing public health challenge worldwide. Excitingly, the extensive clinical application of traditional Chinese medicine may suggest a new direction to combat cancer, and the therapeutic effects of active ingredients from Chinese herbal medicine on cancer are now being widely studied in the medical community. As a traditional anticancer Chinese medicine, ChanSu has been clinically applied sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 129 publications
0
15
0
Order By: Relevance
“…Modern research shows that it has various pharmacological activities such as cardiotonic, antitumor, analgesic, anti-inflammatory, and immune regulation ( Zhan et al, 2020 ). Bufadienolides are the most important bioactive substances in Chan Su, including bufalin, bufotalin, cinobufagin, cinobufotalin, telocinobufagin, etc ( Jia et al, 2022 ). They can effectively combat various cancers such as liver cancer, osteosarcoma, colorectal cancer, gastric cancer, lung cancer, and breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Modern research shows that it has various pharmacological activities such as cardiotonic, antitumor, analgesic, anti-inflammatory, and immune regulation ( Zhan et al, 2020 ). Bufadienolides are the most important bioactive substances in Chan Su, including bufalin, bufotalin, cinobufagin, cinobufotalin, telocinobufagin, etc ( Jia et al, 2022 ). They can effectively combat various cancers such as liver cancer, osteosarcoma, colorectal cancer, gastric cancer, lung cancer, and breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that all the approved drugs contain the extraction of toad venom but not the isolated active components such as these discussed bufadienolides in this review. For example, while Chansu injection, an approved drug in China for infective diseases, has been evaluated for its potential in cancer treatment, its effectiveness and safety among cancer patients are yet to be proved ( Jia et al, 2022 ). A clinical study, published in 2016 in stage III-IV patients of non-Hodgkin lymphoma, showed that the combination of Chansu injection with EOAP (etoposide, vincristine, cytosine arabinoside and prednisone) failed to improve the therapeutic effect when compared to EOAP group ( Niu et al, 2016 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…These compounds are structurally related, and specially, all of them can be regarded as bufalin’s derivatives, with minor differences at certain position, which are shown and highlighted in Figure 2 . It appears that TVAs have broad-spectrum anticancer potential ( Liu et al, 2019 ; Niu et al, 2021 ; Jia et al, 2022 ). Research has indicated that they, either by single use or as a mixture when combined with other agents, are effective in treating acute myeloid leukemia ( Hirasaki et al, 2022 ), lung cancer ( Xie et al, 2018 ; Li et al, 2021b ; Meng et al, 2021 ), colorectal cancer ( Li et al, 2019 ; Bai et al, 2021 ; Meng et al, 2021 ), liver cancer ( Zhang et al, 2012 ; Zhao et al, 2019 ; Zhang et al, 2020b ; Yang et al, 2021b ), breast cancer ( Zhu et al, 2018 ), oral cancer ( Jo et al, 2021 ), gastric cancer ( Xiong et al, 2019 ), Ehrlich ascites carcinoma ( Giri et al, 2018 ), melanoma ( Pan et al, 2019 ; Zhang et al, 2020c ; Kim et al, 2020 ), nasopharyngeal carcinoma ( Pan et al, 2020 ; Hou et al, 2022 ), osteosarcoma ( Cao et al, 2017 ; Dai et al, 2018b ; Zhang et al, 2019a ), cholangiocarcinoma ( Ren et al, 2019 ), myeloma ( Baek et al, 2015 ), etc.…”
Section: Bufadienolides In Toad Venom and Their Therapeutic Implicati...mentioning
confidence: 99%
“…Cancer is a common disease globally that seriously affects human health. Recent studies have illuminated that CBF suppressed the growth of a wide variety of tumor cells, including liver cancer, osteosarcoma, melanoma, colorectal cancer, acute promyelocytic leukemia, nasopharyngeal carcinoma, multiple myeloma, breast cancer, and gastric carcinoma [ 15 ]. The anticancer activities and related mechanisms of CBF are listed in Table 1 .…”
Section: Pharmacological Activities Of Cbfmentioning
confidence: 99%